Effect of TiO(2) rutile nanorods on the photoelectrodes of dye-sensitized solar cells - Jung, Young Hee (Springer, 2013)
In order to enhance the electron transport on the photoelectrodes of dye-sensitized solar cells, one-dimensional rutile nanorods were prepared using electrospun TiO(2) nanofibers. The grain size of the nanorods increased with increasing temperature. Electrochemical impedance spectroscopy measurements revealed reduced interface resistance of the cells with the one-dimensional rutile nanorods due to the improved electron transport and the enhanced electrolyte penetration. Intensity-modulated photocurrent/photovoltage spectroscopy showed that the one-dimensional rutile nanorods provided the electrons with a moving pathway and suppressed the recombination of photogenerated electrons. However, an excessive quantity of rutile nanorods created an obstacle to the electrons moving in the TiO(2) thin film. The photoelectrode with 7 wt.% rutile nanorods optimized the performance of the dye-sensitized solar cells.